Sexual conflict and plasticity in the fruit fly - Filice, David (My University, 2020)
Animals display considerable phenotypic variation in their mating traits, and this variation can have important consequences for the evolution of dimorphic traits between the males and females within a species. In chapter 1, I outline the current state of our understanding of plasticity in reproductive phenotypes, and argue that more work needs to be done to connect the gap between plasticity in mating traits and the outcomes of sexual conflict. Across my four data chapters, I used the fruit fly as a model organism in series of experiments that attempt to better understand how plasticity in mating traits influences the fitness outcomes of both males and females. In chapter 2, I experimentally manipulated the outcome of a fighting experience, and found that males who win a previous fight have higher precopulatory reproductive success, but losers perform better in post-copulatory areas. In chapter 3, I manipulated the amount of competition that a male experiences and found that females mated to males who experience competition produce more early-life offspring but live shorter lives compared to females mated to males that experience no competition. In chapter 4, I manipulated the intensity of sexual conflict that a female experiences and found that males mated to females who experience high conflict have lower pre- and post-copulatory reproductive success compared to males mated to females who experience low conflict. In chapter 5. I manipulated the degree of sexual aggression that a female experiences, and found that females that experience harassment and mating from a male that displays high sexual aggression is subsequently less choosy compared to females that experience a less aggressive male. Finally, in chapter 6, I discuss the significance of my results as they relate to the evolution of reproductive traits in males and females.
Keywords: sexual conflict; phenotypic plasticity; drosophila melanogaster; evolution; behaviour; genetics; sexual selection; mate choice